Changes in EEG amplitude (Alpha and Beta waves) with Thermal environment - Tiago-Costa, E (2016)
When executing a task, brain activity can be observed through electric waves recorded in different frequency bands. The main ones are the Alpha, Beta, Theta and Delta waves. According to some authors, Alpha and Beta waves are related with cognitive capacity and, their presence and evolution, with an individual alertness. In this study, the intention was to evaluate how brain activity is directly influenced by temperature and humidity while performing a task. Therefore, a set of laboratory tests were undertaken to simulate sedentary work in two different thermal environments: 18ºC - 40% (cold) and 35ºC - 80% RH (hot). In the hot thermal environment, oscillation on Alpha waves amplitude suggests an alternation between periods of tiredness with periods in which concentration increases. Regarding Beta waves in the cold thermal environment, most of the time Beta activity is typically higher than that verified in the hot thermal environment. (c) The author; licensee Universidad Nacional de Colombia.